Achalasia: Outcome in children. Issue 2 (February 2017) - Meyer, Anell; Catto‐Smith, Anthony; Crameri, Joe; Simpson, Di; Alex, George; Hardikar, Winita; Cameron, Donald; Oliver, Mark
Abstract: Background: Oesophageal achalasia is well‐recognized but relatively rare in children, occasionally appearing as the "triple A" syndrome (with adrenal insufficiency and alacrima). Treatment modalities, as in adult practice, are not curative, often needing further interventions and spurring the search for better management. The outcome for syndromic variants is unknown. We sought to define the efficacy of treatments for children with achalasia with and without triple A syndrome. Methods: We conducted a retrospective analysis of presentation and outcomes for 42 children with achalasia presenting over three decades to a major pediatric referral center. Long term impact of the diagnosis was assessed by questionnaire. Results: We identified 42 children including six with triple A syndrome. The median overall age at diagnosis was 10.8 years and median follow‐up 1593 days. Initial Heller myotomy in 17 required further interventions in 11 (65%), while initial treatment with botulinum toxin ( n = 20) was ultimately followed by myotomy in 17 (85%). Ten out of 35 patients who underwent myotomy required a repeat myotomy (29%). Patients with triple A syndrome developed symptoms earlier, but had delayed diagnosis, were more underweight at diagnosis and at last follow up. Questionnaire results suggested a significant long term deleterious impact on the quality of life of children and their families. Conclusion: Many children with achalasia relapse after initial treatment, undergoing multiple, different procedures, despite which symptoms persist and impact on quality of life. Symptoms develop earlier in patients with triple A syndrome, but the diagnosis is delayed and this has substantial nutritional impact.